Life cycle assessment of cocoa farming sustainability by implementing compound fertilizer - I. Idawati; N.A. Sasongko; A.D. Santoso; A.W. Sani; H. Apriyanto; A. Boceng (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The global competitiveness of the cocoa processing industry is enhanced through the implementation of technical policies as a sustainable economic sector. The effort is motivated by the potential of large cocoa production and the international market demands for the industry to apply innovative, effective technology and comply with sustainability standards (environment, social, and economic). Therefore, this study aimed to analyze the environmental impact assessment of cocoa production from upstream to downstream processes in North Luwu Regency, South Sulawesi.METHODS: Data were collected from 321 respondents actively working and had at least 8 years of experience in cocoa cultivation and production. Respondents included staff of the Masagena Farmers’ Cooperative from Chalodo Sibali Resoe Industry, Masamba City, and North Luwu Regency, and the secondary data were obtained from a literature review. In addition, the environmental impact was determined using the Midpoint Recipe method and the ecoinvent 3.8 database. This was conducted based on the International Standard Organization of life cycle assessment 14040 and 14044 with a function unit of 1 kilogram chocodate cashew production.FINDINGS: The results showed that reducing chemical fertilizer was environmentally preferable to decreasing all the impact categories assessed since the total potential global warming impact from chocodate cashew production was 2.092 kilogram carbon dioxide equivalent. In this context, electricity and fertilizer were the main contributors to environmental pollution, accounting for 0.438 kilogram carbon dioxide equivalent and 0.215 kilogram carbon dioxide equivalent at 20.97 percent and 10.27 percent, respectively.CONCLUSION: The reduction in the use of inorganic nitrogen, phosphate, potassium fertilizer, from 3.75 to 1.25 kilogram perkilogram cocoa, or the adoption of bio-based nitrogen, phosphate, potassium fertilizer at a rate of 2.5/ kilogram, could substantially mitigate the environmental impact. This mitigation resulted in a 16 percent decrease in global warming potential, reducing from 2.092 to 1.745 kilogram carbon dioxide equivalent. In addition, valuable insights were provided into the scope of life cycle assessment studies and contributed to the selection of sustainable cacao farming systems. These results could be relevant to life cycle assessment practitioners, stakeholders, and governments in offering valuable insights for the formulation of policies and programs for developing cacao farming in the future.